Effects of excavating-sponge removal on coral growth. (11th August 2015) - Halperin, Ariel A.; Chaves-Fonnegra, Andia; Gilliam, David S.
Abstract : Some excavating sponges are strong competitors for space on coral reefs, able to kill live coral tissue and to overgrow entire coral colonies. Stony corals with excavating sponges can die or become dislodged. To date no restoration efforts to eliminate excavating sponges from live corals have been considered. In this study we examined the effect and remedial potential of removal of the excavating sponge, Cliona delitrix, by monitoring tissue loss of the stony coral Montastrea cavernosa . Thirty-three corals colonized by the sponge were used: 11 as controls, and 22 as treatments in which sponges were removed using hammer and chisel. After sponge removal, resultant cavities in the coral skeletons were filled with common cement or epoxy. Standardized photos of each coral were taken immediately after sponge removal, and at 6 and 12 months afterwards. Results were similar between fill materials and showed a reduction in coral tissue loss in colonies where the sponge was removed. This study demonstrates that eliminating the bioeroding sponge enables potential recovery in affected stony corals after a year. However, 36% of experimental corals showed renewed presence of C. delitrix on the colony surface within a year after removal, demonstrating the extraordinary ability of this sponge to colonize corals. Although the technique used in this study is applicable to enhance modern coral restoration practices by slowing tissue loss, this method is costly, elaborate, and not suitable at a reef-wide scale. Further restoration alternatives and long-term measures to prevent over-colonization of corals by excavating sponges are encouraged.